Development and validation of the leadership learning agility scale - Bouland-van Dam, Sophie I. M.; Oostrom, Janneke K.; Jansen, Paul G. W. (Frontiers in Psychology, 2022)
Using a combination of both deductive and inductive approaches and established scale development and validation procedures, we developed the Leadership Learning Agility Scale (LLAS). We administered the LLAS among three independent samples of workers and leaders (N = 907; N = 196; N = 219). Our results indicate that our 18-item LLAS measures the willingness to learn from social experiences, and the drive to apply those lessons in new and challenging leadership roles, and comprises a Developing Leadership, Seeking Feedback, and Developing Systematically dimension. Furthermore, the LLAS showed adequate internal consistency. Leadership learning agility was positively related to achievement motivation, extraversion, and conscientiousness but unrelated to openness to experience.